(untitled) (Malaysian Management Journal, 1995)
The process of R&D screening is a very important component of any R&D organization and must be done continuously. At Guthrie Research Chemara, such screening has been an integral part of research. R&D screening has a direct value in making decisions as to which research proposals should be included in or excluded from R&D programs which, eventually, will influence the corporate strategy of the Company. Screening involves a whole range of internal vetting before justified R&D proposals are prioritized, approved and implemented. Also, one of the major elements of the screening process, the cast and profit calculation of research proposals, greatly assists in the rapid commercialization of R&D findings. This paper relates some of the experiences from Guthrie Research Chemara on the usefulness of R&D screening for effective research.